2021
DOI: 10.5037/jomr.2021.12301
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Alveolar Ridge Augmentation with an Autogenous Bone Block Graft Alone with or without Barrier Membrane Coverage: a Systematic Review and Meta-Analysis

Abstract: Objectives: To test the hypothesis of no difference in implant treatment outcome following lateral alveolar ridge augmentation with autogenous bone block graft with or without barrier membrane coverage. Material and Methods: PubMed (MEDLINE), Embase and Cochrane library search in combination with a hand-search of relevant journals was conducted. Human studies published in English until the 8 th of February 2021 were included. Randomised controlled trials with an observation period longer than three months were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In cases when neither less invasive alternatives, such as narrow or short implants, nor removable prostheses were possible or accepted by a patient, several augmentation techniques have been widely documented: among these, many authors have indicated the use of autogenous bone blocks as the gold standard since they have good osteogenetic, osteoinductive, and osteoconductive properties. Nevertheless, the harvesting procedure may imply postoperative complications as well as limited availability and a higher degree of resorption compared to other grafts [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases when neither less invasive alternatives, such as narrow or short implants, nor removable prostheses were possible or accepted by a patient, several augmentation techniques have been widely documented: among these, many authors have indicated the use of autogenous bone blocks as the gold standard since they have good osteogenetic, osteoinductive, and osteoconductive properties. Nevertheless, the harvesting procedure may imply postoperative complications as well as limited availability and a higher degree of resorption compared to other grafts [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, according to a recent systematic review, postoperative dimensional changes in the augmented bone seem to diminish with the use of barrier membrane coverage [18].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the latter aspect, block grafting was considered in the reported cases due to the advanced defect dimensions and the potential advantage of block grafts of remaining more stable and robust against graft displacement upon wound closure and healing. There is a lack of evidence supporting the use of barrier membranes with bone block grafting [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, none of the complications were reported by the patient in the present case. Interestingly, the combination of chin graft with particulate bone grafts covered by a collagen membrane has yielded gain in bone dimensions in the present case and as a result [21][22][23].…”
Section: Prementioning
confidence: 99%